A Three-Component, One-Pot, Sequential Synthesis of a Common Tetrasaccharide Block Related to the Lipopolysaccharide of the Escherichia Coli O9, Klebsiella pneumonia O3, and Hafnia alvei PCM 1223 - Maity, Sajal Kumar; Ghosh, Rina (Synlett, 2012)
An expeditious three-component, one-pot, sequential synthesis of a common block tetrasaccharide fragment Manp-(1→3)-Manp-(1→2)-Manp-(1→2)-Manp related to the pentasaccharide repeating unit of the O-antigen of Escherichia Coli O9, Klebsiella pneumonia O3, and Hafnia alvei PCM 1223 with minimal protecting group manipulation is reported.
Keywords: three-component; one-pot; tetrasaccharide; Escherichia coli O9; Klebsiella pneumonia O3